1996
DOI: 10.1007/bf00731481
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the action of ceramide-like substances (d- andl-PDMP) on sphingolipid glycosyltransferases and purified lactosylceramide synthase

Abstract: We have studied the effects of D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP) and its L-enantiomer on glycosphingolipids in cultured normal human kidney proximal tubular cells. We found that D-PDMP exerted a concentration-dependent reduction in the metabolic labelling and cellular levels of glucosylceramide (GlcCer), lactosylceramide (LacCer), and the globo-series glycosphingolipids, GbOSe3Cer and GbOse4Cer. It also directly inhibited the activity of UDP-glucose:ceramide beta 1--> 4-glucosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Because VEGF induced LacCer synthase activity, we first used D-PDMP, initially shown to be an inhibitor of GlcCer synthase 31 but later proven to be an inhibitor of purified LacCer synthase. 28,32 Our studies provided evidence that VEGF-induced LacCer/GlcCer synthesis, PECAM-1 gene/protein expression, and angiogenesis was inhibited by D-PDMP in a dose-dependent fashion. Moreover, this inhibitory effect was by passed by LacCer but not GlcCer, suggesting that VEGF targets the LacCer synthase to induce angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Because VEGF induced LacCer synthase activity, we first used D-PDMP, initially shown to be an inhibitor of GlcCer synthase 31 but later proven to be an inhibitor of purified LacCer synthase. 28,32 Our studies provided evidence that VEGF-induced LacCer/GlcCer synthesis, PECAM-1 gene/protein expression, and angiogenesis was inhibited by D-PDMP in a dose-dependent fashion. Moreover, this inhibitory effect was by passed by LacCer but not GlcCer, suggesting that VEGF targets the LacCer synthase to induce angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Because L-PDMP is a potent activator of LacCer synthase, 16,28 we examined whether this compound may alter PECAM-1 expression and angiogenesis. L-PDMP significantly induced PECAM-1 expression (supplemental Figure IIA) and angiogenesis (supplemental Figure IIB).…”
Section: L-pdmp Stimulates Pecam-1 Expression and Tube Formation/angimentioning
confidence: 99%
“…D -PDMP was initially suggested to be a selective inhibitor of GlcT-1 with an IC 50 of ∼10 µ M [23], but subsequent studies revealed that it also inhibits GalT-2 (with equal potency), two of the globo-series synthases [15], and the sialyltransferase that converts LacCer to ganglioside GM3 [24]. Treatment of NIH 3T3 fibroblasts or kidney proximal tubular cells with D -PDMP reduced the cellular levels of GlcCer and LacCer and increased the levels of Cer in a concentration- and time-dependent fashion [15, 25]. The functional groups comprising D -PDMP (the acyl group in amide linkage, the phenyl group, and the morpholine) have provided sites for substitutions when attempting to design more selective GlcT-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…NAC, gelatin, lucigenin, GlcCer, dimethylsulfoxide (DMSO) and phosphate-buffered saline (PBS) were from Sigma Chemical Company. D -PDMP, an inhibitor of GlcT-1 and GalT-2 activities [15, 16], was purchased from Matreya, Inc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation